Bandung as an International Relations Actor Through the Collaboration of Bandung and Fort Worth Sister City in International Leadership Academy Program - Putra, Reynaldi Mandala; Rachman, Junita Budi; Dermawan, Windy (International Journal of Social Science and Business, 2022)
The City Government is one of the actors who are starting to get involved in the international world.Â  On the other hand, cities are seen as agencies in 'global governance' that work together to solve global problems global. This study aims to explain the city of Bandung in presenting itself as an actor of international relations through the implementation of the sister city cooperation between the city of Bandung and the city of Forth Worth in the International Leadership Academy (ILA) program. The research method used is qualitative research with data collection through interviews and literature studies. Meanwhile, the conceptual framework used consists of the concept of international cooperation and the concept of sister city. From 2010 to 2021 the Bandung city delegation, namely high school students, accompanied by supervisors and employees participated in the ILA program which is held every year in the City of Fort Worth. The presence of this delegation represented the city of Bandung as an international relations actor. Through ILA activities in the city of Fort Worth with Bandung high school students as delegates, the city of Bandung is guaranteed its presence in the international arena almost every year. But unfortunately, the Bandung City Government did not fully support the ILA youth exchange program activities held in the city of Fort Worth. Even though this support is important to maintain the continuity of the presence of the City of Bandung as an actor in international relations.